Implementasi Marketing Public Relations dalam Live Shopping Instagram Geggo Women - Kukuh Mudawisika; Nurrahmawati (UNISBA Press, 2022)
Abstract. Currently, the technological era has begun to develop rapidly, as well as a dynamic marketing public relations Implementation following its development. Various companies, especially in the clothing sector, are competing to market their products through various social media such as Instagram, Tiktok, and so on. Likewise with Geggo Women. Geggo Women is a hijab brand that stands under the auspices of PT. Latallah Jaya Abadi. Geggo Women has a unique selling method, which is called live shopping. Geggo Women maximizes the features provided on Instagram, because Instagram is the main medium in marketing their products. This live shopping uses the live feature. Geggo Women do this live shopping for 2 days, and every day Geggo Women live for 2 hours. On this occasion, the author made a research on